Kajian dan Tinjauan Pendidikan Islam di Madrasah - Dewi Pertamasari; Muhammad Yusron Maulana El – Yunusi (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2024)
We know that Indonesia as a Muslim country. Majority of Indonesia humans are Muslims. So, not only mosque, but also so many Islamic schools in Indonesia too. We called it Madrasah. Madrasah one of places can uses by Muslims to study about Islamic education. Beside it, the important thing of this Islamic study is ontological philosophy. Why? Because from the ontological philosophy there are some several important that we can search like the nature of Islamic study, the goals of this Islamic study, even the people who will be subject of this study and the curriculum in Islamic education at madrasah itself. So, from the explanation before, the writer has the purpose of this research is to examine about Islamic Study especially to Madrasah through ontological philosophy. Descriptive qualitative method used by the writer which is focus on this research and observation so far. The writer hopes this research can be used and will be given some knowledge about Islamic education especially to Madrasah through ontology philosophy to everyone. And also, can be given the best think and understood of Islamic education as like as our hope.